2005
DOI: 10.1007/s00425-005-0016-z
|View full text |Cite
|
Sign up to set email alerts
|

Thaxtomin A induces programmed cell death in Arabidopsis thaliana suspension-cultured cells

Abstract: Thaxtomin A is the main phytotoxin produced by Streptomyces scabiei, the causative agent of common scab disease of potato. Pathogenicity of S. scabiei is dependent on the production of thaxtomin A which is required for the development of disease symptoms, such as growth inhibition and cell death. We investigated whether thaxtomin A-induced cell death was similar to the hypersensitive cell death that often occurs in response to specific pathogens or phytotoxins during the so-called hypersensitive response (HR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
1
9

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 71 publications
3
84
1
9
Order By: Relevance
“…Thus, both types of cell death are likely to share common mechanistic elements (Greenberg and Yao, 2004). Interestingly, NLP Pya -or NLP Vd -induced plant cell death is accompanied by fragmentation of nuclear DNA (Veit et al, 2001;Wang et al, 2004) that resembles that caused by the cytolytic phytotoxin, thaxtomin A from Streptomyces scabiei (Duval et al, 2005). We found that NLP-induced PCD is light dependent and requires active plant metabolism.…”
Section: Nlps Induce a Distinct Type Of Pcdmentioning
confidence: 84%
“…Thus, both types of cell death are likely to share common mechanistic elements (Greenberg and Yao, 2004). Interestingly, NLP Pya -or NLP Vd -induced plant cell death is accompanied by fragmentation of nuclear DNA (Veit et al, 2001;Wang et al, 2004) that resembles that caused by the cytolytic phytotoxin, thaxtomin A from Streptomyces scabiei (Duval et al, 2005). We found that NLP-induced PCD is light dependent and requires active plant metabolism.…”
Section: Nlps Induce a Distinct Type Of Pcdmentioning
confidence: 84%
“…The mechanism of auxin inhibition of thaxtomin A toxicity is not determined. Thaxtomin A has been reported to induce programmed cell death (PCD) in exposed plant tissues (12). Recently, Gopalan (13) demonstrated PCD could be reversed by treatment with auxins 2,4-D and IAA.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have suggested that necrotrophic fungal pathogens can also manipulate the host during infection in subtle ways (Govrin and Levine 2000). To determine whether V. dahliae uses supernatant-induced cell death to manipulate its host, tobacco leaves were infiltrated with cycloheximide (CHX) (an inhibitor of protein synthesis) and actinomycin D (ActD) (an inhibitor of RNA synthesis), together with V. dahliae supernatant (Duval et al 2005). CHX efficiently delayed the development of leaf lesions ( Fig.…”
Section: Proteins Related To Cell Deathmentioning
confidence: 99%